Bibliotheken. Innovation aus Tradition. Rolf Griebel zum 65. Geburtstag Libraries: Tradition-Based Innovation. For Rolf Griebel on his 65th Birthday - Hermann, Martin (De Gruyter, 2014)
This commemorative volume honors the 65th birthday of Dr. Rolf Griebel, celebrating his service as General Director of the Bavarian State Library. The authors include major contributors to German and international library science from the realms of culture, academia, and politics. The essays explore the strategic challenges that face innovate library management practice, focusing on the future role of libraries in a digital world.